Learning to inhabit the liquid liminal world of work: An auto-ethnographic visual study of work-life boundary transitions. Issue 2 (April 2023) - Izak, Michal; Shortt, Harriet; Case, Peter
This article explores a conceptually modified notion of liminality in order to make better sense of contemporary 'flexible' working life. Previous conceptualizations of liminality rely on the assumed existence of socially sustained boundaries and the possibility of boundary spanning. Under conditions of liquid modernity, however, boundaries or thresholds have been destabilized to the point of collapse. Nonetheless, individuals still feel the need to establish and maintain intersubjective boundaries to preserve their own sense of well-being. To understand the new predicament faced by employees, we reconceptualise liminality for liquid times – through the notion of liquid liminality – and, simultaneously, problematize dominant conceptions of work-life balance. The implications that liquid liminality carries for the notion of flexible knowledge work are discussed. Our auto-ethnographic visual study of an academic returning from maternity leave uses a socio-material lens to exemplify the struggles of the contemporary flexible knowledge worker. It also demonstrates how the constant transition between workplace and home life is freighted with anxiety and exhaustion. We also outline opportunities for establishing new learning habits that follow from our theoretical framing and empirical analysis.